Food and sustainability: the water footprint assessment of the menus served in a university restaurant (Sustainability in Debate, 2024)
The current agro-food system requires an intense exploitation of natural resources. “Sustainable diets” proposes a production model that considers both health and the preservation of natural resources. Given that university restaurants consume significant amounts of food in virtue of meal preparation, the use of indicators such as the Water Footprint (WF) is a vital tool for assessing the use of natural assets across these locals. This study aims to analyse the relationship between WP and the sustainability of the menus served in the Federal Institute of Piauí (IFPI), São João do Piauí campus restaurant. This is a quantitative, cross-sectional research which points out that animal-based foods, especially beef, present a high level of WF. In addition, the lack of vegetarian options on the menus was observed. These findings indicate the need to reformulate the menus under analysis so that they are more in line with the principles underlying sustainability.